2019
DOI: 10.17323/jle.2019.7995
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Business English with TED Talks: Putting Ideas into Practice

Abstract: TED.com is used in teaching EFL to enhance exposure to English, to promote authentic vocabulary and to develop multiple foreign language skills. For university students studying business as their major and English for professional communication as a part of their university curriculum, TED talks provide a cutting-edge business context, which aims to increase the learners’ English language proficiency, develop the learners’ professional competencies and expand their outlook by acquainting them with business pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Learning a foreign language is undoubtedly a complex process as one has to master both language skills and systems (Hundarenko, 2019;Hojatpanah & Dashtestani, 2020;Kapranov, 2020;Lacková, 2019;Leláková & Šavelová, 2020;Putrawan, 2019;Stognieva, 2019;Todaka, 2020) in order to become an effective language user. Moreover, language conveys knowledge as well as cultural data and it mirrors the important and specific thoughts of individuals (Namaziandost, Sabzevari & Hashemifardnia, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Learning a foreign language is undoubtedly a complex process as one has to master both language skills and systems (Hundarenko, 2019;Hojatpanah & Dashtestani, 2020;Kapranov, 2020;Lacková, 2019;Leláková & Šavelová, 2020;Putrawan, 2019;Stognieva, 2019;Todaka, 2020) in order to become an effective language user. Moreover, language conveys knowledge as well as cultural data and it mirrors the important and specific thoughts of individuals (Namaziandost, Sabzevari & Hashemifardnia, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, while the overall effect and most country-level effects were positive, some individual studies still found negligible or negative impacts of TED Talks on speaking skills (Mıcık & Rızaoğlu, 2024;Salem, 2019). These findings underscore the importance of carefully considering learner needs, proficiency levels, and instructional design when integrating TED Talks into language classrooms (Aziz & Ngadiron, 2019;Hidayati & Suharyadi, 2023;Stognieva, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…In another Spanish context, Rodríguez- Arancón and Calle-Martínez(2014) study the multi-person collaborative writing system to improve various business English qualities and skills [ 7 ]. In Russia, Stognieva (2019) uses various TED speech resources in business English teaching to enhance learners' English levels, professional qualities and understanding about business practices around the world [ 8 ]. In the United Arab Emirates, Albers, Vences and Nickerson (2020) in their study improve pre-experience business English learners’ electronic communication skills (i.e.…”
Section: Literature Reviewmentioning
confidence: 99%